Technological education challenge: an European perspective - Impedovo, Maria Antonietta; Ginestié, Jacques; Williams, John (Australasian Journal of Technology Education, 2017)
This paper is a reflection on Technological education in the light of the changes that this subject has undergone recently. The first part of the paper provides a theoretical presentation of Technological education from a European perspective. Then a more specific exploration is developed focussing on the middle schools in two selected contexts (France and Italy), considered here as examples of curriculum. Finally, the implications of this subject on current society are explored.Â